Analysis of Village Funds Financial Management Planning in Air Dingin Village in Kaur District - Neri Susanti; Rinto Noviantoro; Ali Imran (Kusuma Negara Business School, 2021)
The purpose of this research is to find out how the financial management planning in the Air Dingin Village of Kaur Regency and whether the village financial management plan in the Air Dingin Village of Kaur Regency is in accordance with the village financial management plan according to the Minister of Home Affairs Regulation number 113 of 2014. The data collection method uses a questionnaire and documentation and the data analysis method used is the analysis method used, which is to compare the Financial Management Planning Process made by the Air Dingin Village of Kaur Regency with the Minister of Home Affairs Regulation number 113 of 2014. The results of this study are the process of financial management planning Village Fund Allocation in the Air Dingin Village begins with the preparation of the RPJMDesa, RKPDesa and APBDesa. In general, the financial management planning process of Village Fund Allocation (ADD) in Desa Air Dingin has been in accordance with Permendagri number 113 of 2014. However, there is one article or provision that has not been implemented, namely article 20 paragraph 4